Acidosis Improves Uptake of Antigens and MHC Class I-Restricted Presentation by Dendritic Cells - Vermeulen, Elba Monica (2004)
It is widely appreciated that inflammatory responses in peripheral tissues are usually associated to the development of acidic microenvironments. Despite this, there are few studies aimed to analyze the effect of extracellular pH on immune cell functions. We analyzed the impact of acidosis on the behavior of dendritic cells (DCs) derived from murine bone marrow. We found that extracellular acidosis (pH 6.5) markedly stimulated the uptake of FITC-OVA, FITC-dextran, and HRP by DCs. In fact, to reach similar levels of endocytosis, DCs cultured at pH 7.3 required concentrations of Ag in the extracellular medium almost 10-fold higher compared with DCs cultured at pH 6.5. Not only the endocytic capacity of DCs was up-regulated by extracellular acidosis, but also the expression of CD11c, MHC class II, CD40, and CD86 as well as the acquisition of extracellular Ags by DCs for MHC class I-restricted presentation. Importantly, DCs pulsed with Ag under acidosis showed an improved efficacy to induce both specific CD8+ CTLs and specific Ab responses in vivo. Our results suggest that extracellular acidosis improves the Ag-presenting capacity of DCs.